Abdominal obesity is associated with impaired cognitive function in euthymic bipolar individuals. (2nd October 2016) - Lackner, N.; Bengesser, S.A.; Birner, A.; Painold, A.; Fellendorf, F.T.; Platzer, M.; Reininghaus, B.; Weiss, E.M.; Mangge, H.; McIntyre, R.S.; Fuchs, D.; Kapfhammer, H.P.; et al.
Abstract : Objectives. Overweight/obesity has been implicated to play a role in cognitive deficits in bipolar disorder (BD). This study aims to identify the relationship between body fat distribution and different domains of cognition in BD during euthymia. Methods. A sample of 100 euthymic individuals with BD was measured with a cognitive test battery (i.e., Trail Making Test-A-B/TM-A/B, d2 Test of Attention, Stroop test, California Verbal Learning Test/CVLT) and an anthropometric measures set (body mass index, waist circumference, hip circumference, waist-to-hip-ratio, waist-to-height-ratio, and lipometry). Patient data were compared with a healthy control group ( n = 64). Results. Results show that overweight patients with BD exhibit lower performance in the TMT-A/B as well as in the free recall performance of the CVLT compared to normal-weight patients with BD and controls. In bipolar individuals, (abdominal) obesity was significantly associated with a poor cognitive performance. In bipolar females, associations with measures of verbal learning and memory were found; in bipolar males, associations with poor performance in the TMT-A/B and in the Stroop interference task were demonstrated. In controls, no associations were found. Conclusions. There are several possible pathways moderating the association between obesity and cognition in BD. Anthropometric and lipometry data underline the substantial mediating impact of body fat distribution on cognition in BD.